Organizational Commitment, Job Satisfaction, and Locus of Control on Employee Turnover Intention and Performance at PT. Sekarbumi Alam Lestari - Habibi; Achmad Tavip Junaedi; Sudarno; Sarli Rahman; Mujtaba M. Momin (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study is to determine and analyze organizational commitment, power, and flexibility of control affect turnover intention and employee performance of PT. Sekarbumi Alam Lestari. The population in this study is PT. Sekarbumi Alam Lestari in Kampar district employs 185 employees while the research sample as the unit of observation is referred to as the census technique. So the number of samples in this study found 185 employees of PT. Sekarbumi Alam Lestari in Kampar district. The data analysis technique in this study used descriptive analysis and PLS structural equation model analysis (SEM). The results of this study indicate that the organizational commitment variable is significant in turnover intention. The job satisfaction variable has no effect on turnover intention. Locus of the control variable is significantly positive on turnover intention. Organizational commitment variable has a significant effect on employee performance. The job satisfaction variable has no effect on employee performance. Locus of control variable has a significant effect on employee performance. The turnover intention variable is significantly positive on employee performance.